Optimization of Domestic Wastewater Treatment Using a Mixture of Coconut Shell Activated Carbon Adsorbent and Fly Ash (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
Utilization of solid waste raw materials in the form of coconut shells and fly ash as adsrobents for domestic wastewater treatment. This study aims to optimize the effect of coconut shell activated carbon and fly ash with variations in mass ration and stirring time on changes in pH, COD, BOD, ammonia, TSS, and total coliform by adsorption on domestic liquid waste to meet waste quality standards. The research method includes the preparation of activated carbon from coconut shell, SEM characterization and experiments of a mixture of coconut shell activated carbon mass and fly ash (5:10, 10:5, 5:15, 15:5 grams) with variations in stirring time (30 minutes, 60 minutes). The results of the study, the most optimal mixture for changes in pH, ammonia, TSS, COD, BOD, total coliform parameters in domestic wastewater was a mixture of coconut shell activated carbon adsorbent mass of 15 grams and fly ash of 5 grams with a stirring time of 60 minutes.